The Community Service Report on Education Unit Assistance to Accelerate the Implementation of the Independent Curriculum (IKM) - Feby Elra Perdima; Mesterjon Mesterjon; Soef Sugiyanto; Mirwan Apendi (Jurnal Dehasen Untuk Negeri, 2023)
The Merdeka Mengajar Platform is a technology platform provided to become a driving partner for teachers and principals in teaching, learning and creating. The Merdeka Mengajar Platform was built to support the implementation of the Merdeka Curriculum so that it can assist teachers in getting references, inspiration, and understanding in implementing the Merdeka Curriculum. Recently, to overcome the learning crisis due to the Covid-19 pandemic, the Minister of Education, Culture, Research and Technology (Kemendikbudristek) Nadiem Anwar Makarim launched the 15th Merdeka Learning Episode, namely the Free Curriculum and the Freedom Teaching Platform, online, Friday ( 11/2). Minister Nadiem revealed, referring to various national and international studies, the learning crisis in Indonesia has been going on for a long time and has not improved from year to year. The learning crisis is increasing due to the Covid-19 pandemic which has caused learning loss and increased learning gaps.